Implementasi Pemikiran Paul Ricoeur dalam Pendidikan Agama Kristen untuk Menghadapi Permasalahan Krisis Identitas Remaja - Indah Istapawati; Andreas Adu Rihi; Maria Yuliasti; Eko Junianto (SERVITA DEI : Jurnal Teologi dan Pendidikan Kristen, 2025)
The identity crisis experienced by young people is marked by confusion of meaning, social media pressure, and the loss of a grand narrative that unites life. This study aims to discuss practical strategies for applying Paul Ricoeur’s thought in Christian Education to address the identity crisis of students. This research employs a library study with a descriptive qualitative approach, analyzing Ricoeur’s seminal works along with recent literature on Christian education and adolescent development. The findings highlight four strategies: (1) creating a safe classroom space to share life stories, (2) applying narrative hermeneutics in light of students’ experiences, (3) training students to write faith reflections, and (4) forming a faith community as a healthy collective identity. The novelty of this study lies in integrating Ricoeur’s narrative identity philosophy with Christian pedagogy in the Indonesian context, showing that narrative hermeneutics provides a framework to shape students’ spirituality amid identity crises.